2001
DOI: 10.1046/j.1365-2796.2001.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and cardiovascular risk in French and Swedish automotive industry workers – cross sectional results from the Renault–Volvo Coeur study

Abstract: . Kumlin L, Latscha G, Orth‐Gomér K, Dimberg L, Lanoiselée C, Simon A, Eriksson B, the Coeur Study Group (Health Department, Volvo Aero Corporation, Trollhättan, Sweden; Service Medical, Renault Automobiles, Billancourt, France; Department of Preventive Medicine, Karolinska Institute, Stockholm, Sweden; The World Bank, Washington DC, USA; Broussais Hospital, Paris, France; and Nordic School of Public Health, Gothenburg Sweden). Marital status and cardiovascular risk in French and Swedish automotive industry wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Previous studies have shown that workers in automotive assembly plants reported high levels of job stress [1][2][3][4][5] . For instance, Karasek et al's 3) cross-sectional study highlighted high strain work (high demand and low control) in machine-paced operative assemblers.…”
Section: Prevalence Of Self-perceived Depression Anxiety and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that workers in automotive assembly plants reported high levels of job stress [1][2][3][4][5] . For instance, Karasek et al's 3) cross-sectional study highlighted high strain work (high demand and low control) in machine-paced operative assemblers.…”
Section: Prevalence Of Self-perceived Depression Anxiety and Stressmentioning
confidence: 99%
“…Studies have shown that job stress was a significant problem in automotive assembly line workers [2][3][4][5][6] . Karasek 3) highlighted high strain work (high demand and low control) among machine-paced operative assemblers.…”
mentioning
confidence: 99%
“…Gliksman et al showed that Australian men aged ≥65 yr who had never married had low average HDL-cholesterol, and that those living alone had high average SBP 6) . However, Kumlin et al 8) and Ben-Shlomo et al 11) in a study of French, Swedish and English workplaces found that CVD risk factors did not differ between married men and those who had never married. We found here, that Japanese married men had fewer CVD risk factors and less clustering of multiple risk factors than those who had never married.…”
Section: Discussionmentioning
confidence: 93%
“…Current smoking rates, blood pressure, total cholesterol and plasma glucose were higher in Group N, than in Group M. Group N had more of 4 CVD risk factors than the Group M. The difference in risk factor clustering between Groups M and N was more evident among men who lived with others than among those who lived alone. Many Western reports have described the relationship between marital status and all-cause mortality 1-6, 11, 12) , CVD mortality 1,2,4,5) or CVD risk factors [6][7][8][9][10] . Johnson et al examined the effect of marital status on mortality in a cohort of 281,460 men and women aged 45 yr and older in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation